Characteristics and outcomes of gastroduodenal ulcer bleeding: a single-centre experience in Lithuania - Petrik, Pavel; Brašiškienė, Saulė; Petrik, Eglė (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Introduction : Despite the optimal use of combined endoscopic haemostasis and pharmacologic control of acid secretion in the stomach, mortality in patients with peptic ulcer bleeding (PUB) has remained constant. Recent data has shown that the majority of patients with PUB die of non-bleeding-related causes. Aim : To provide an overview of our experience of PUB management, with emphasis on the effect of age, gender, comorbidities, and drug use on the characteristics and outcomes of gastroduodenal ulcer bleeding. Material and methods : We retrospectively reviewed the medical records of all patients admitted with the primary diagnosis of acute, chronic or unspecified gastric and/or duodenal ulcer with haemorrhage during 2008–2012. Results : Two hundred and nineteen patients were identified. 46.6% of patients were ≥ 65 years old (elderly) and 53.4% were < 65 years old (young). The young patients were more likely to have duodenal ulcers and liver failure at admission. Previous use of medications was more regularly observed in gastric ulcer patients than in duodenal ulcer patients. Rebleeding occurred in 43 (19.6%) patients and death in 5 (2.3%) patients. Increased risk of mortality in our patients was associated with age ≥ 65 years (RR = 2.21; 95% CI: 1.90–2.56; p = 0.021). Conclusions : Management of peptic ulcer bleeding should aim at reducing the risk of multiorgan failure and cardiopulmonary death instead of focusing merely on successful haemostasis.